KEBERADAAN PENGETAHUAN LOKAL MASYARAKAT TANI DI ERA REVOLUSI HIJAU (STUDI KASUS PETANI PADI DI DESA CAREBBU KECAMATAN AWANGPONE KABUPATEN BONE PROVINSI SULAWESI SELATAN) - Andi Anizha Rahmadani; Tamzil Ibrahim; Saadah Saadah (Hasanuddin University, 2020)
AbstractThis study aims to analyze the existence of indigenous knowledge of peasant society on farming management especially of rice land farming in The Village of Carebbu, Awangpone Sub-district, Bone Regency, South Sulawesi Province during April 2019. The method used in this study is descriptive qualitative and case study method with a sampling technique that used is purposive sampling and snowball sampling. Researcher use is an in-depth interview and analyzed by qualitative data analysis with the approach of the AGIL functional theory of Talcott Parson. This result shows if there is 8 indigenous knowledge that exists on peasant society from generation to generation on their farming management of paddy rice land, but in the middle of the green revolution, it shows that indigenous knowledge of peasant society is lost some, there are 2 of 8 indigenous knowledge has to begin to be left out. This is due to the thinking of the peasant society which began to change from irrational to rational.Key Words: Indigenous knowledge; farm society; green revolution.